The British Columbia mission, or, Metlahkatlah [electronic resource]. - Duncan, William, 1832-1918.; Church Missionary Society. (London : Church Missionary House, 1871)
Original issued in series : The missions of the Church Missionary Society no. 2. Fourth ed. of Metlahkatlah, or, Ten years' work among the Tsimsheean Indians of British Columbia. Attributed to the Church Missionary Society --Canadiana 1867-1900. Electronic reproduction. Mode of access: Internet. 44